2008
DOI: 10.1080/08820530802007382
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-ophthalmic Sarcoidosis: The University of Iowa Experience

Abstract: In our Midwest retrospective case series of biopsy proven neuro-ophthalmic sarcoidosis, patients were predominately white females with a wide age range. Consideration for the diagnosis of neurosarcoidosis should therefore not be limited by age, gender, or race. Optic neuropathy was the most common manifestation, typically presenting with optic disc edema and severe visual loss. No light perception vision was relatively common and should be considered a "red flag" for the diagnosis. Contrast cranial MRI frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 32 publications
3
49
2
1
Order By: Relevance
“…A review of 20 patients with NS and optic nerve involvement demonstrated that with long term treatment, vision improved in one-third of patients, stabilize in one-third, and worsen in one-third. The ophthalmologic course was described as chronic in 5 (25 %), relapsing-remitting in 8 (40 %) and resolved or stable in 7 (35 %) patients [25]. Our experience is that 3/4 patients had stabilization of their visual field deficits and one patient There is no consensus about treatment goals in HP NS and no controlled prospective trials were done in this field.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A review of 20 patients with NS and optic nerve involvement demonstrated that with long term treatment, vision improved in one-third of patients, stabilize in one-third, and worsen in one-third. The ophthalmologic course was described as chronic in 5 (25 %), relapsing-remitting in 8 (40 %) and resolved or stable in 7 (35 %) patients [25]. Our experience is that 3/4 patients had stabilization of their visual field deficits and one patient There is no consensus about treatment goals in HP NS and no controlled prospective trials were done in this field.…”
Section: Discussionmentioning
confidence: 91%
“…Optic atrophy is the most common neuro-ophthalmologic manifestation of patients with NS [24,25]. In patients with sarcoidosis in general, anterior uveitis is the most common cause of change in vision [26].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular involvement has been reported in 21 ophthalmological sarcoidosis has been reported to cause cranial neuropathies, Horner's syndrome, tonic pupil, and anterior and posterior optic pathway disease. 4 Ingestad and Stigmar divided optic nerve involvement due to sarcoidosis into five categories: optic disc oedema secondary to posterior uveitis; optic disc oedema secondary to raised intracranial pressure; optic neuritis; optic atrophy secondary to compression or infiltration from a primary central nervous system lesion; and primary granuloma of the optic nerve head. 5 In this case there was left optic neuritis and a right optic nerve head and peripapillary granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…During a mean follow-up period of 18.75 months, 84.6% of patients showed a complete response to the treatment, but 19.2% of patients developed further signs of sarcoidosis [34]. However, optic neuropathy, typically presenting with optic disc edema and severe visual loss has been described as a common manifestation of sarcoidosis [37].…”
Section: Wegener's Granulomatosis and Sarcoidosismentioning
confidence: 98%